Investigating the Impact of Transport Services and Renewable Energy on Macro-Economic and Environmental Indicators - Liu, Jinghua; Quddoos, Muhammad Umer; Akhtar, Muhammad Hanif; Amin, Muhammad Sajid; Yu, Zhang; Janjua, Laeeq Razzak (Frontiers in Environmental Science, 2022)
A global shift towards renewable energy has proved to be a major constituent in drifting towards climate change. Given the context, the present research focuses on the nexus amongst renewable energy (RE), transport services (Trans), and performance on economic and environmental (CO) fronts. The study has employed an ARDL time series approach to test for the effects of hypothesized relationships for the period 1990 to 2019. Results of the study divulge that the consumption of RE is inversely and significantly coupled with the CO, validating the notion that Romania has emerged as a leading renewable energy user. Foreign direct investment inflows (FDI) in Romania are significantly and positively associated with the CO. However, the impact of FDI tends to be smaller than that of the forest area (FA) and RE. All the exogenous variables appear to affect the CO significantly in the short run. Furthermore, the forest area is negatively linked with the CO in the Romanian economy. Based on the outcomes of the research, policy prescriptions are suggested to safeguard environmental degradation and to support growth in forest resources.